Ferromagnetic properties of glucose coated Cu2O nanoparticles - Mahajan, Mangesh B.; Pavan, M. S.; Joy, Pattayil Alias (Solid State Communications, 2009)
Magnetic properties of glucose coated cuprous oxide nanoparticles of different sizes have been studied. Unlike bulk Cu2O, which shows diamagnetic behavior, the nanoparticles show superparamagnetic behavior. A superparamagnetic blocking temperature of 21 K is observed for 5 nm particles. A magnetic hysteresis loop with a coercivity of 406 Oe is observed for these particles at 5 K. The magnetization and the coercivity increase with decreasing particle size. The superparamagnetic behavior, along with the increase in magnetization and coercivity with decreasing particle size, is due to the enhanced surface contributions to the magnetism. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Cuprous oxide; magnetic properties; Nanoparticles

Magnetic characteristics of nanocrystalline multiferroic BiFeO3 at low temperatures - Vijayanand, S.; Mahajan, Mangesh B.; Potdar, H. S.; Joy, Pattayil Alias (Physical Review B, 2009)
The magnetic characteristics of nanocrystalline BiFeO3 with average crystallite sizes of similar to 50 and similar to 100 nm are evaluated by studying the temperature and field dependence of magnetization at low temperatures. Different properties such as magnetization, coercivity, and remanence show evidence for changes in the magnetic properties associated with the phase transitions at low temperatures, reported from Raman studies. Detailed field-cooled and zero-field-cooled magnetization measurements show that the likely origin of the changes in the magnetic characteristics is from the changes in the domain structure.
Keywords: bismuth compounds; coercive force; crystallites; magnetic domains; magnetic transitions; Multiferroics; Nanostructured materials; Raman spectra; remanence

Evolution and magnetic characteristics of NiO-Ni(OH)(2) core-shell nanostructures - Mahajan, Mangesh B.; Joy, Pattayil Alias (Physical Chemistry Chemical Physics, 2013)
The evolution and magnetic behaviour of NiO-Ni(OH)(2) core-shell nanostructures with different thicknesses of the hydroxide shell have been studied. The nickel hydroxide shell is found to alter the magnetic characteristics of nickel oxide at low temperatures and explains the origin of the exchange bias effect due to the anti-ferromagnetic NiO core and a ferromagnetic nickel hydroxide shell.